Plant communities of the desert shrubland in the Tambo and Moquegua rivers basins in the southern Peru - Chicalla Rios, Kent Jonathan (2021)
A study is presented on the floristic composition, phytosociological classification, ecology and bioclimatology of the plant communities in the desert environments of the Tambo and Moquegua river basins in the department of Moquegua, located in southern Peru at an elevation of about 1350 and 3200 m s.n.m. 94 phytosociological surveys were carried out in the field following the Braun-Blanquet method adapted by Montesinos, TWINSPAN 2.3 software was applied to classify vegetation and CANOCO 4.5 for the analysis of DCA with environmental variables. In the bioclimatic classification the Rivas-Martínez method was followed. The results show 181 species of flora are recorded, of which 32 are endemic and 121 are native. Vegetation analysis and classification result in the description of three associations, 5 new sub-associations and two communities within the new Ambrosio artemisioidis-Weberbauerocerion torataensis alliance belonging to the order Oreocereo leucotrichi-Neoraimondietalia arequipensis and class Opuntietea sphaericae. Two tropical bioclimatic classifications were found: Termotropical and Mesotropical in combination with four levels of humidity or ombroclimates: Ultrahyperarid, Hyperarid, Arid and Dry. The vegetation of the arid environments in southern Peru can become very varied and restricted to its river basins, they are dependent on extraordinary humid conditions that allow us to deduce the importance of conserving these desert ecosystems.